Cost-effectiveness of Prophylactic Zika Virus Vaccine in the Americas - Shoukat, Affan; Vilches, Thomas [UNESP]; Moghadas, Seyed M. (Centers Disease Control & Prevention, 2019)
Zika virus remains a major public health concern because of its association with microcephaly and other neurologic disorders in newborns. A prophylactic vaccine has the potential to reduce disease incidence and eliminate birth defects resulting from prenatal Zika virus infection in future outbreaks. We evaluated the cost-effectiveness of a Zika vaccine candidate, assuming a protection efficacy of 60%-90%, for 18 countries in the Americas affected by the 2015-2017 Zika virus outbreaks. Encapsulating the demographics of these countries in an agent-based model, our results show that vaccinating women of reproductive age would be very cost-effective for sufficiently low (<$16) vaccination costs per recipient, depending on the country-specific Zika attack rate. In all countries studied, the median reduction of microcephaly was >75% with vaccination. These findings indicate that targeted vaccination of women of reproductive age is a noteworthy preventive measure for mitigating the effects of Zika virus infection in future outbreaks.